물가동학에서 기대변수의 특성에 대한 연구 - 이재준 (13777, 2014)
This paper attempts to demonstrate the critical role of expectation horizons in economic agents building their expectations for the future. It starts with the analysis of what constraints the economics-based assumption related to information efficiency co